Go west, young Ash ; Ash Ketchum, Pokemon detective - West, Tracey, 1965- (New York, New York : Scholastic Inc., 2021)
Ash, Pikachu, and friends travel through the deep, dark forest on their way to the Wild West, encountering a theft, a rescue, and a mystery to solve along the way.Ash, go! Is a Pokemon lost, missing or acting strange? Ash Ketchum, Pokemon P.I., is on the case. With the help of is friends and trusty sidekick, Pikachu, Ash is solving mysteries involving Pokemon like Hoothoot, Spinarak and Stantler.
Text bound back-to-back and inverted.
Keywords: Pokemon (Fictitious characters) -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Friendship -- Juvenile fiction; Upside-down books